Influence of SiC/TiB2 Particles Addition on Corrosion Behavior of As-Cast Zn-Al-Cu Alloy Hybrid Composites - Rohinikumar Chebolu; Ramanaiah Nallu; Ratnam Chanamala; Surender Kumar Sharma; Ramesh Rudrapati (Journal of Engineering)
In this work, the silicon carbide (SiC) and titanium diboride (TiB2) reinforced as-cast Zn-Al-Cu alloy-based hybrid composites were produced with ultrasonic-assisted stir casting. The corrosion behavior of as-cast Zn-Al-Cu/TiB2/SiC hybrid composites with varying 0, 5, 10, and 15 weight percent of SiC + TiB2 particulates in Zn-Al-Cu matrix alloy was investigated in this study, The effect of additional reinforcements content on the corrosion behavior of hybrid composites with respect to Zn-Al-Cu alloy was investigated. The corrosion rate of hybrid composites was taken by using potentiodynamic polarization equipment (with 3.5 wt.% NaCl solution). The potentiodynamic polarization test findings showed that the hybrid composites’ uniform and localized corrosion resistances were enhanced by the addition of dual reinforcements. As the weight fraction of the SiC/TiB2 reinforcement increases, weak microgalvanic cells that form between the constituent phases of the fabricated as-cast Zn-Al-Cu hybrid composites weaken, improving their resistance to uniform and localized corrosion. The results revealed that the corrosion rate values were reduced to 28.88% at 15% of reinforcement when compared to the base alloy.